Dentro da caverna de Amaterasu: os imaginários sobre a diferença e o fenômeno do estigma de jovens do Centro da Juventude Professor Jomar Vieira da Rocha no município de Cascavel/PR - Mendes, Marlon Jose Gavlik (2018)
Human's sociability is a complex and dynamic phenomenon. We learned ways to socialize with other people up from the beginning. Some of these behaviors are based on differentiation, aggression or peaceful coexistence. When an individual has divergent features from other people of his socializing life and becomes to be belittled due to these characteristics, he begins to be perceive as he has some stigma. Adolescence and youth are significant for constructions, deconstructions and reconstructions of the experience of sociability, including the processes of difference and stigma. This research aimed to describe the imaginary of youngsters about the alterity lived in social relations, identifying the characteristics, types and / or attributes that the youth consider different from themselves or the group they belong to and how they relate to whom or which is considered different. So, adolescence and youth are significant for constructions, deconstructions and reconstructions of sociability experiences, including in the processes of difference and stigma. Thus this study was carried out taking into account these issues, and it aims at describing the imaginary of young people regarding the otherness experienced in social relationships, as well as identifying which characteristics, types and/or attributes are considered as different by the adolescents when they look at their own features or the group to which they belong and how they relate to what is considered different. Therefore, as a data collection instrument, semi-structured interviews were applied with 8 adolescents from Professor Jomar Vieira da Rocha Youth Center in Cascavel/PR. And the concepts of formist sociology were also used as a tool to analyze the collected data. Among the imaginary obtained, attributes related to sexuality and gender, as well as body, clothing, body adornments, disabilities and groups of belonging are significant for the relationships construction based on difference, both when it is seen in a derogatory way, which stimulates aggression and exclusion as well as when it becomes a valued attribute. The speech also plays a unique role in youth sociability, since it is a classificatory parameter in order to differ people. It also sets the way stigma happens. On the other hand, the speech can be a means to reduce stigmatizing relationships, which also provides more respectful and welcoming sociability as far as diversity is concerned. Both difference and stigma are dynamic processes and are expressed in a complex and volatile way in youth’s lives. Thus, it is expected that this research contributes to the studies on these phenomena, in such a way that it can stimulate other researches and contribute to a more respectful and valuing world concerning diversities in all its demonstrations.